Distinct impacts of growth band on the mechanical properties of abalone nacre under compressive and tensile stresses - Liang, S. M.; Ji, H. M.; Li, X. W.
In abalone nacre, growth bands occur periodically with the change of living environments. To explore the specific role of growth bands playing in the mechanical properties of nacre, the compressive and three-point bending behaviors of composites with growth bands in green abalone shell and pure nacre without growth bands in whitened ear abalone shell were comparatively investigated. It is found that the mechanical effects of growth bands under different stress states are significantly distinct, mainly attributing to the different responses of organic matrix interlayer in growth bands. Specifically, due to the remarkable ductility of thicker organic matrix interlayer under the action of compressive stress, the growth bands could be bent without fracturing in the region of kink band. However, the existence of growth bands leads to a lower interfacial strength, finally causing the fact that the composites with growth bands exhibit a lower strength but a higher toughness than pure nacre under uniaxial compression tests. Contrastively, both the strength and toughness of the composites are lower than those of pure nacre under three-point bending tests, since micro-cracks will be first initiated in growth bands on account of the weaker organic matrix interlayer under tensile stress. Therefore, the growth bands actually play different roles in the mechanical performances of nacre under compressive and tensile stresses.
Keywords: ABALONE SHELL; NACRE; GROWTH BAND; COMPRESSIVE BEHAVIOR; THREE-POINT BENDING BEHAVIOR; KINK BAND